Selenium and plants - Mateja GERM; Vekoslava STIBILJ (Acta Agriculturae Slovenica, 2007)
Selenium is of metabolic importance in cyanobacteria and in some plants, being involved in their antioxidative processes. Selenium is widely distributed on the Earth’s surface and available for plants in at least small traces. Cultivation of plants enriched with selenium could be an effective way of producing selenium rich foodstuffs and thereby increase health benefits. The essentiality of selenium to higher plants is still under debate. Selenium can increase the tolerance of plants to UV-induced oxidative stress, delay senescence, and promote the growth of ageing seedlings. Recently it has been shown that selenium has the ability to regulate the water status of plants under conditions of drought. The distribution and speciation of selenium in plants and the effect of selenium alone and in combination with some other environmental parameters is discussed.